Novel implementation of IoT based non-invasive sensor system for real-time monitoring of intravenous fluid level for assistive e-healthcare. Issue 3 (5th August 2019) - Ray, Partha Pratim; Thapa, Nishant; Dash, Dinesh; De, Debashis
Abstract : Purpose: The purpose of the study is to design and develop an pervasive and smart Internet of Things (IoT)-based sensor system to monitor he real-time intravenous (IV) fluid bag level. Design/methodology/approach: This paper investigates such issue and performs several experiments to develop a non-invasive, semi-automatic system to monitor IoT-based IV fluid level in real-time. Findings: The outcome of this study is a prototype hardware that includes an ESP8266 based embedded Web server to disseminate the fluid exhaust status flag to its connected users. Nurses can get the prompt intimation about the status of IV fluid bag whether it is about to get empty. Research limitations/implications: IoT is the backbone of the proposed system. Multi-master system need to be studied in future. Practical implications: Non-invasive and real-time IoT-based novel technique is developed with power-efficient and cost-effective pervasive sensors. Social implications: This is applicable for pervasive and assistive e-health-care services by care givers and medical professionals. Originality/value: The deployed system is controlled by ATtiny85 with help of LM35 temperature sensor. The results show a promising future of the proposed development in enhancing IoT-based smart health-care service in the coming days.